Pengaruh Pendidikan dan Pelatihan Digital Forensik terhadap Kualitas Penanganan Kasus Kejahatan Siber - Abdul Sakti (Populer: Jurnal Penelitian Mahasiswa, 2025)
This research aims to explore the influence of digital forensics education and training on the quality of handling cyber crime cases. With the increasing complexity of cybercrime, it is important for law enforcement to have adequate skills in digital forensics. The research method used is qualitative with a case study approach in several law enforcement agencies. The research results show that effective education and training can improve investigators' abilities in identifying, collecting and analyzing digital evidence, thereby improving the quality of handling cyber crime cases. In addition, collaboration between investigators and digital forensic experts has been proven to increase the effectiveness of investigations. However, challenges such as limited resources and legal understanding remain obstacles that need to be overcome. Therefore, recommendations to improve education and training programs in the field of digital forensics are very necessary to face the growing threat of cybercrime.